Interactions in MOOCs: The Hidden Part of the Iceberg - Cisel, Matthieu Tenzing (International Review of Research in Open and Distributed Learning, 2018)
Interactions that take place between MOOC users outside of discussion forums, and out of the reach of course designers, have received little attention from the scientific community despite their potential influence on learner retention. Based on an online survey, we found that MOOCs are often used as an activity among friends and family, and not exclusively in the academics or in the workplace. Interactions between course users may continue beyond of the boundaries of the course, and sometimes into other MOOCs. These various interactions include collaborative tasks, as well as tasks which should be performed individually, such as assessments. This work illustrates the mismatch that can appear between prescribed and actual tasks, and the potential importance of interactions between users, to address the isolation that contributes to low retention rates for online learners.